L8r, g8r - Myracle, Lauren, 1969- (The Internet girls, 2014)
Throughout their senior year in high school, Zoe, Maddie, and Angela continue to share "instant messages" with one another about their day-to-day experiences as they consider college, sex, the importance of prom, and the inevitable end of their inseparable trio.